Design, Development, and Evaluation of a Microgrid for the Energy Management in a Small Poultry - Saavedra, Jr., Nicasio (JPAIR Multidisciplinary Research, 2019)
The Development of an Energy Management System for a Small Poultry is another solution to help the poultry raisers/farmers obtain a reasonable and renewable source of energy. A microgrid can be characterized by its integration of distributed energy resources and controllable loads. Such integration brings unique challenges to the microgrid management and control which can be significantly different from conventional power systems. The developed device is composed of the following major components: brooder, where the chicks are placed, and the electronic devices are installed; a relay which monitors and controls the power supply of the system; a solar panel and battery that captures and saves the energy from the sun; and an inverter that converts direct current to alternating current. The total power of the poultry is 33W and used 560W per day of the power source from the battery. Test results showed that the contribution of saving power consumption reached 83% and losses are 35.75%. The voltage of the battery in 100% reached to 12.4V down to 2% has 10.45V. The actual testing for amperes of the bulb is 2.5A, the counter has 0.6A, and the temperature has 0.25A. The actual wattage of bulb is 30W, and temperature has 3W. The performance of the prototype was evaluated by twenty (20) panel of evaluators composed of electronic technicians and engineers, agriculturists, and poultry farmers using the Technological University of the Philippines (TUP) Evaluation Instrument for Prototype Developed. The prototype got a grand mean of 4.72 with a descriptive rating of â€œExcellentâ€ which proves that the project reduces the consumption of electricity from the commercial power distribution.